2018
DOI: 10.1080/23744235.2018.1449961
|View full text |Cite
|
Sign up to set email alerts
|

Successful outcome for patients with streptococcal prosthetic joint infections – a retrospective population-based study

Abstract: This study indicates an acceptable success rate for the patients treated with DAIR strategy, and a high overall success rate for episodes suffering streptococcal PJIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…However only few cases had this course of treatment. When comparing with other common pathogens, we found that the cure rate of 72% for DAIR-treated cases was well in line with treatment outcomes for staphylococci (55-88%) and streptococci (75-84%) [9,10,17,18]. However, we did not compare PJIs caused by these pathogens and we found no other studies comparing enterococcal PJI with staphylococcal or streptococcal PJI either.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However only few cases had this course of treatment. When comparing with other common pathogens, we found that the cure rate of 72% for DAIR-treated cases was well in line with treatment outcomes for staphylococci (55-88%) and streptococci (75-84%) [9,10,17,18]. However, we did not compare PJIs caused by these pathogens and we found no other studies comparing enterococcal PJI with staphylococcal or streptococcal PJI either.…”
Section: Discussionmentioning
confidence: 68%
“…Enterococcal PJIs are frequently poly-microbial, and have been associated with a higher failure rate than both staphylococcal and streptococcal PJIs [7,9,10]. Two-stage exchange of infected prostheses is therefore the generally recommended surgical treatment modality, and one-stage exchange is considered contraindicated [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of DAIR for treating periprosthetic infection caused by Streptococcus is relatively high [ 27 , 28 ]. Lam et al [ 27 ] reported that the initial success rate of DAIR in the treatment of 53 PJI cases caused by Streptococcus infection was 84%.…”
Section: Introductionmentioning
confidence: 99%
“…The success rate of DAIR for treating periprosthetic infection caused by Streptococcus is relatively high [ 27 , 28 ]. Lam et al [ 27 ] reported that the initial success rate of DAIR in the treatment of 53 PJI cases caused by Streptococcus infection was 84%. However, in 2017, a large multicenter retrospective study showed that the success rate of DAIR for Streptococcus infection was only 57.9% [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…When prosthetic infection has been diagnosed, whether group G streptococcal infection or otherwise, standard practice has been to undergo open irrigation and debridement with potential explant. However, new literature has demonstrated successful treatment of streptococcal joint infection with the more conservative debridement, antibiotics, and implant retention technique [18]. In addition, Burkert and Watanakunakorn found that only 1 in 13 patients with group G streptococcal PJI required explant [19].…”
Section: Discussionmentioning
confidence: 99%